Ask questions and get helpful answers.

How do we evaluate limit of,

lim x-> 0 [ln(x+1)/( (2^x) - 1)]

I tried using the substitution x+1 = e^k , when x tends to 0 so does k, which gave out,

lim k->0 [ k/((2^((e^k) - 1)) -1 ) ]

which I simplified into( for the ease of use let e^k =a)

lim k->0 [k/( ((2^a)/2) - 1)]

lim k->0 [2k/((2^a) -2 )]

which sums up to,
(2*0)/((2^(e^0)) - 2)

(2*0)/(2-2)

which gives out an undefined value as 0/0

How do we solve this?

  1. 👍
  2. 👎
  3. 👁
  4. ℹ️
  5. 🚩

1 answer

  1. How about good old L'Hopital's rule

    lim x-> 0 [ln(x+1)/( (2^x) - 1)]
    = lim x-> 0 [1/(x+1) / (ln2*2^x)
    = (1/1)/(ln2 ( 1)
    = 1/ln2 = appr 1.44269..

    check: let x = .0001 in the original
    = ln(1.0001) / (2^.0001 - 1)
    = 1.4425 , not bad, my answer is correct

    1. 👍
    2. 👎
    3. ℹ️
    4. 🚩

Answer this Question

Related Questions

Still need help?

You can ask a new question or browse existing questions.